The Role of Lecturers in Guiding Students' Communication Ethics on Social Media (Islamic Cyber Ethics Perspective) - Sri Ayu Rayhaniah; M. Tahir; Andik Riyanto; Sri Ayu Rayhaniah; M. Tahir (Universitas Negeri Malang, 2026)
The development of social media as a digital communication space has changed the communication practices of students, including Islamic Communication and Broadcasting students who use it as a digital da'wah medium. However, the high intensity of social media use is not always accompanied by adequate awareness of communication ethics, so it has the potential to give rise to communication practices that are not in accordance with Islamic communication values. This study aims to analyze the role of lecturers in guiding Islamic Communication and Broadcasting students' communication ethics on social media from the perspective of Islamic cyberethics. This study uses a qualitative approach with a descriptive study design through in-depth interviews with eight lecturers of Islamic Communication and Broadcasting at Islamic Religious Universities in Indonesia who were selected by purposive sampling. Data analysis was carried out using thematic analysis techniques with reference to the principles of Islamic communication ethics, namely qaulan sadida, qaulan baligha, qaulan karima, qaulan ma'rufa, and qaulan layyina. The results of the study show that lecturers have a strategic role as facilitators of internalizing the ethical values of Islamic communication, supervisors of the use of polite language, directors of information verification, role models in digital communication practices, feedback on digital content, shaping social responsibility awareness, directing ethical digital da'wah practices, controllers of communication behavior in cyberspace, and mediators in online communication conflicts. This study concludes that the integration of Islamic communication ethical values in the digital media-based learning process contributes to forming honest, polite, non-provocative, and responsible student communication practices on social media.